Vaginal Lesion with Placental Site Trophoblastic Tumor after Partial Molar Pregnancy – A Case Report - Vorisek, Carina; Bokun, Magda; Zeppernick, Felix; Enzensberger, Christian; Gattenlöhner, Stefan; Meinhold-Heerlein, Ivo (Archives of Clinical and Medical Case Reports, 2020)
Background: Gestational trophoblastic neoplasia (GTN) is a rare disease developing after normal or molar pregnancy. Clinical presentation can be heterogenous while early detection of GTN is crucial for treatment success. We report a rare case with vaginal location of placental site tumor (PSTT) after suction curettage of partial molar pregnancy. Case Report: We report a 25 year-old gravida III, para I patient with partial molar pregnancy and following placental site tumor located at the left vaginal wall. The patient presented with heavy vaginal bleeding and persistent human chorionic gonadotropin (β-hCG) levels twenty-five days after suction curettage. Due to persistent β-hCG levels and histology report suggesting PSTT, chemotherapy with methotrexate (MTX) was started and lead to curation of the disease after 11 cycles of treatment. Conclusion: GTN clinical presentation as well as tumor location can vary. β-hCG estimations after partial molar pregnancy are crucial for early diagnosis.